Influencia de la contaminación atmosférica en la fachada de rascacielos, caso Torre Colpatria - Romero, Nydia; Dupuy, C.; Quiñones, J. (Revista ALCONPAT, 2011)
The materials of the facade of the Colpatria Tower have been degraded by physical and chemical phenomena, detaching of blocks of different sizes. A thorough survey of the pathological processes was carried out, in order to analyze the origin and consequences of the damage; samples of mortar and concrete were characterized by petrographic analysis and carbonation. The results showed that the main causes of deterioration were cracking, carbonation and sulfate attack, caused by air pollution. Also it was established that the aggressiveness of these phenomena is directly related to factors such as height, depth of damage in relation to environmental pollution, the orientation of the facade and climatic factors such as wind and rain. Keywords: air pollution; precast concrete; facade; petrographic analysis; carbonation.